Suppressing pre-hydrolysis in TiO2 manufacturing: Design optimization of an indirect heating hydrolysis system - Han Junhee; Kim Hyojung; Lee Dohyung (Chemical Industry and Chemical Engineering Quarterly)
The particle size of 𝑇𝑖𝑂2 is critically influenced by the operation of the hydrolysis process. Failure to achieve uniform particle size during hydrolysis can have significant repercussions on subsequent processes, such as washing, reduction, and bleaching procedures, ultimately leading to the production of unusable final products. The primary goal of this study is to suppress pre-hydrolysis, which is a factor that impedes the formation of uniform particles during the hydrolysis procedure. To overcome this issue, the researchers designed an indirect heating system to mitigate the pre-hydrolysis phenomenon. For designing an indirect heating system, multiphase Computational Fluid Dynamics (CFD) simulations were performed. The proposed optimized design was then implemented and tested in the actual field. The success of the field test was evaluated through settling value tests conducted on the hydrolyzed solution, and the uniformity of particle size was analyzed using Transmission Electron Microscopy (TEM) images, Scanning Electron Microscope (SEM), and Microtrac. The findings of this study demonstrate the effective application of the developed multiphase CFD simulation in enhancing the hydrolysis process for the production of anatase titanium dioxide particles. This successful integration demonstrates the application of mechanical engineering techniques in the field of chemical engineering.